Mangan süperoksit düsmutaz (mnsod) ala16val gen polimorfizmlerinin koroner arter olaylarında koruyucu rollerinin araştırılması ; Investigation of the preventive roles of manganese superoxide dismutase (mnsod) ala16val gene polymorphism in coronary artery events - Atmaca, Hale (My University, 2013)
MANGAN SÜPEROKSİT DİSMUTAZ (MnSOD) ALA16VAL GEN POLİMORFİZMİNİN KORONER ARTER OLAYLARINDA KORUYUCU ROLLERİNİN ARAŞTIRILMASI Çalışma, 43 koroner arter hastası ve 58 koroner arter hastası olmayan bireyde uygulandı. MnSOD geni Ala16Val genotipleri kantitatif polimeraz zincir reaksiyonu (PZR) yöntemi ile saptandı. MnSOD geni Ala16Val polimorfizmi için genotip sıklıkları KAH grubunda C/ C (Homozigot yabanil tip), C/ T (Heterozigot), T/ T (Homozigot polimorfik tip) genotipler için sırasıyla % 20.9, %41.9, % 37.2 ve KAH olmayan grupta %15.5, %51.7, %32.8 olarak tesbit edildi. Her iki çalışma grubumuzda MnSOD geni Ala16Val polimorfizmlerinden heterozigot genotiplerin sıklığı, homozigot yabanil tip ve homozigot polimorfik tipteki genotiplerin sıklığından yüksek olarak saptandı. Tüm çalışma grubumuzdaki mitokondriyal MnSOD aktiviteleri, MnSOD geni Ala16Val genotiplerine göre karşılaştırıldığında homozigot yabanıl genotip taşıyıcılarının en yüksek, homozigot polimorfik genotip taşıyıcılarının en düşük MnSOD aktivitesine sahip olduğu belirlendi. Koroner arter hastalığı bulunmayan çalışma grubunda MnSOD Ala16Val polimorfizminin yağsız vücut kütlesi (p=0.01) ve yağ kütlesi (p=0.05) üzerine anlamlı etkileri olduğu saptandı. Heterozigot genotipe sahip (C/ T) koroner arter hastalığı bulunmayan kişilerdeki yağsız vücut kütlesi ve yağ kütlesi değerlerinin homozigot yabanıl genotipteki (C/ C) kişilere oranla daha düşük olduğu gözlendi. Tüm çalışma grubunda ise sadece yağsız vücut kütlesi değerlerinin MnSOD genotipleri tarafından etkilendiği ve heterozigot genotipteki bireylerin yağsız vücut kütlelerinin homozigot yabanıl ve homozigot polimorfik genotipteki bireylere kıyasla daha düşük olduğu belirlendi. KAH grubunda MnSOD geni Ala16Val polimorfizminin beslenme alışkanlıklarına etkileri belirlendi. Ala16Val polimorfizminin heterozigot genotipe sahip KAH’larında yağdan zengin gıdalarla beslenme alışkanlıkları diğer genotiplere kıyasla daha düşük seviyelerde görülürken, homozigot polimorfik genotipe sahip KAH’larının diğer genotiplere kıyasla proteinden fakir beslenme alışkanlıklarını benimsedikleri görüldü. Tüm çalışma grubu değerlendirildiğinde ise MnSOD Ala16Val genotiplerinin beslenme alışkanlıkları ile anlamlı bir etkileşim göstermediği ve sadece yağsız vücut kütlesi üzerinde etkisinin varlığı saptandı.

INVESTIGATION OF THE PREVENTIVE ROLES OF MANGANESE SUPEROXIDE DISMUTASE (MNSOD) ALA16VAL GEN POLYMORPHISM IN CORONARY ARTERY EVENTS The study was performed in 43 patients with coronary artery disease and 58 patients without coronary artery disease. MnSOD gene Ala16Val genotypes were determined with quantitative polymerase chain reaction (PCR) method. MnSOD Ala16Val genotype frequencies were determined as 20.9%, 41.9%, 37.2% respectively for C/ C (homozygous wild type), C/ T (heterozygous), T/ T (homozygous polymorphic type) genotypes in the coronary artery disease patients; whereas 15.5%, 51.7% and 32.8% for the patients without coronary artery disease. The frequency of heterozygous genotypes of MnSOD gene Ala16Val polymorphism was found to be higher than homozygous wild-type and homozygous genotypes in both study groups. In our total study group, the homozygous wild type genotype carriers were detected to have the highest, whereas homozygous polymorphic genotype carriers were detected to have the lowest mitochondrial MnSOD activities when compared according to MnSOD Ala16Val genotypes. In the patients without coronary arttery disease, MnSOD Ala16Val polymorphism was found to have significant effects on lean body mass (p=0.01) and fat mass (p=0.05). The lean body mass and fat mass values were found to be lower in the heterozygous (C/ T) individuals compared to homozygous wild type (C/ C) in the patients without coronary artery disease. Whereas in the whole study population, only the lean body mass was found to be effected by MnSOD genotypes and heterozygous individuals to have lower lean body mass levels in comparison to homozygous wild type and homozygous polymorphic. The effects of MnSOD gene Ala16Val polymorphism on eating habits was also evaluated. In CAD disease patients with Ala16Val polymorphism heterozygous genotype nutritional habits rich in lipids were lower to that of other genotypes, whereas CAD patients with homozygous polymorphic genotype was detected to prefer poor protein diet. When all the study group was evaluated, MnSOD Ala16Val genotypes were not found to have statistically significant relationship with nutritional habits, but found to be effective only on lean body mass.All values in the study group of lean body mass is only affected by the MnSOD genotype homozygous and heterozygous genotypes of individuals homozygous for the wild and polymorphic genotypes were lower than the individuals. Ala16Val MnSOD gene polymorphism in patients with CAD were the effects of nutrition alışkalıklarına. Heterozygous genotypes with CAD compared to oil-rich foods, eating habits, low levels of other genotypes, whereas homozygous genotypes of polymorphic was adopted by poor eating habits. In the entire study group evaluated Ala16Val MnSOD genotypes show a significant interaction with dietary habits and not just an effect on lean body mass were.
Keywords: Çevre Mühendisliği